Koncepcja metody kombinatorycznej rozwiązywania układów równań liniowych - Kisiel, Jerzy (The Conception of the Combination Method for Solution of Linear Systems Equations, 2006)
In this paper a conception of the combination method for resolving linear systems in space of wholes numbers is described. This method can be successfully used for resolving a lot of tasks in the management of economics systems, e.g. real estate managing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (16); 2006; nr 1100, s. 147-151